2016
DOI: 10.1038/hdy.2016.39
|View full text |Cite
|
Sign up to set email alerts
|

Demographic history and adaptation account for clock gene diversity in humans

Abstract: Circadian clocks give rise to daily oscillations in behavior and physiological functions that often anticipate upcoming environmental changes generated by the Earth rotation. In model organisms a relationship exists between several genes affecting the circadian rhythms and latitude. We investigated the allele distributions at 116 000 single-nucleotide polymorphisms (SNPs) of 25 human clock and clock-related genes from the 1000Genomes Project, and at a reference data set of putatively neutral polymorphisms. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Furthermore, Hu et al (2016) reported that a GWAS analysis of self-reported morningness showed 15 significantly associated loci, including seven circadian genes [52]. These findings as well as other reports [53][54][55][56][57] suggest that genes with circadian expression may play a critical role in regulating both the circadian clock and sleep homeostasis as well as circadian-related sleep disturbances such as advanced sleep phase syndrome (Table 1).…”
Section: Genes Related To Advanced Sleep Phase Syndromesupporting
confidence: 60%
“…Furthermore, Hu et al (2016) reported that a GWAS analysis of self-reported morningness showed 15 significantly associated loci, including seven circadian genes [52]. These findings as well as other reports [53][54][55][56][57] suggest that genes with circadian expression may play a critical role in regulating both the circadian clock and sleep homeostasis as well as circadian-related sleep disturbances such as advanced sleep phase syndrome (Table 1).…”
Section: Genes Related To Advanced Sleep Phase Syndromesupporting
confidence: 60%
“…If indeed the latitudinal effect exists, ultraviolet radiation (UVR), which is received in an inverse latitudinal manner, may be the relevant environmental agent. Environmental-neurophysiological interfaces have already been established in mice with seasonally-related, light-induced, mTOR and BDNF signalling-related dendritic morphologic adaptation [ 78 ], while UVR’s neurological role is thought to involve at least sleep duration [ 79 ], clock gene diversity [ 80 ], and development of multiple sclerosis [ 81 ]. In the case of IS, the UVR-epileptic interaction may be mediated by Vitamin D3, the secosteroid synthesized cutaneously in an UVR-dependent fashion, although infants primarily derive it from maternal contribution [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…While longitude and latitude do not act directly on organisms, they serve as composite variables representing multiple environmental factors, any one or a combination of which could be exerting parallel selective forces. Latitude has been found to be associated with circadian clock genes in Drosophila 78 81 and humans 82 , 83 , and now in honeybees. Clock genes are tagged by SNPs forming latitudinal and longitudinal gradients in Iberia.…”
Section: Discussionmentioning
confidence: 99%